EFL Teachers’ Professional Development. A Narrative Inquiry into Lesson Planning During the Pandemic (2023)
This narrative inquiry explored how an EFL teacher’s lived experiences during the pandemic helped her to reconstruct her lesson plans as a manifestation of professionalism. Her students were adults with unfinished schooling from the prioritized curriculum. Data was collected through interviews, lesson plans, a reflective journal, and WhatsApp screenshots. Results showed that her classes were limited to brief text, voice, and video messages. There was no individual or immediate feedback. The dialogic interaction during the narrative inquiry was a mediational tool that activated the teacher’s reflections on her past lessons, which guided her to adjust her present and future pedagogical practices.